Download presentation
Presentation is loading. Please wait.
Published byAdam Lester Modified over 6 years ago
1
Lesson 3.1: Solving Equations using Addition or Subtraction
Inverse Operations: math operations that undo each other Examples: 1) Addition and Subtraction 2) Multiplication and Division Goal when solving Equations: - Get the variable by itself on one side of the equation
2
Addition Property of Equality: Adding the SAME number to BOTH SIDES of an equation results in an equivalent equation –Equation is still true Subtraction Property of Equality: Subtracting the SAME number from BOTH SIDES of an equation results in an equivalent equation – Equation is still true ***Can do anything you want to an equation, as long as you do the SAME to BOTH SIDES. Golden Rule of Algebra: Do unto one side as you do unto the other. B.S. of Algebra : Both Sides
3
To solve an equation: 1) Simplify each side of equation Use inverse operation - Ask yourself “What is being done to the variable?” - You do the INVERSE Operation to BOTH SIDES of the equation Example: Solve. SHOW ALL WORK STEPS 1) x - 2 = -14 1) x - 2 = -14 x – = x + (-2) + 2 = x = -12 OR x + (-2) = -14 x + (-2) – (-2) = -14 – (-2) x + (-2) + 2 = x = -12
4
x + (-11) = 8 x + (-11) – (-11) = 8 – (-11) x + (-11) + 11 = x = 19 Ck. x + (-11) = 8 19 + (-11) = 8 8 = 8 | -10 | + y = -21 10 + y = -21 y + 10 = -21 y + 10 – 10 = -21 – 10 y (-10) = (-10) y = -31 Ck. | -10 | + y = -21 | -10 | + (-31) = -21 10 + (-31) = -21 -21 = -21
5
-x – 7 = 9 -x – = 9 + 7 -x + (-7) + 7 = 9 + 7 -x = 16 x = -16 6 – t = -7 6 + (-t) = -7 -t + 6 = -7 -t + 6 – 6 = -7 – 6 -t (-6) = -7 + (-6) -t = -13 t = 13
6
-x – (-11) = -19 -x – (-11) + (-11) = (-11) -x (-11) = (-11) -x = -30 x = 30
7
Recall: Word problems:
1) Write knows and Finds 2) Write Verbal Model 3) Write Let statement 4) Write Equation 5) Solve using inverse operations
8
Homework: p. 135-136, #22-40 evens, #42-44 all, #46-52 evens
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.